Blood pressure, weight change and incident hypertension after switching to dolutegravir in treatment-experienced people living with HIV - Steffen, Hans Michael; Viola, Evelyn Maria; Thawani, Agness; Kachere, Layout G.; Huwa, Jacqueline; Wallrauch-Schwarz, Claudia; Kasper, Philipp; Neuhann, Florian; Heller, Tom; Winkler, Volker; Rambiki, Ethel; Mahanani, Melani Ratih (AIDS <London>, 2025)
Objective: - Dolutegravir (DTG) is recommended in WHO guidelines and has reportedly been associated with excess gain in body weight (BW). - Design: - In the prospective LighTen Cohort Study (ClinicalTrials.gov NCT02381275) we evaluated changes in BW and blood pressure (BP) of people living with HIV (PLHIV) who had initiated tenofovir (TDF)/lamivudine (3TC)/efavirenz (EFV; TLE). Follow-up continued after participants had been switched to TDF/3TC/DTG (TLD) in 2019. - Methods: - From the electronic medical record system, we retrieved data on BW and systolic BP of LighTen Cohort Study participants (age ≥18 years), who were still in care. We modelled BW and systolic BP over time utilizing interrupted time series (ITS) considering repeated measurements and adjusting for age and sex. Incident hypertension was defined as office BP ≥140/90 mmHg using ≥2 measurements on ≥2 consecutive visits. - Results: - Data of 543 PLHIV (317 females) were analysed. ITS showed an increase in BW of 1.24 kg/year on TLE with a minimal contribution (36.5 g/year) during DTG treatment, in contrast to the change in systolic BP: 0.33mmHg/year on TLE vs. 2.63mmHg/year on DTG. Incident hypertension in previously normotensive PLHIV was confirmed in 5.4% (while on TLE) versus 11.0% (while on TLD). - Conclusions: - Following the initial increase in BW on TLE, a larger increase in BP and a higher risk of incident hypertension was associated with switching antiretroviral therapy from TLE to TLD. Focussing on BP control while on DTG and timely initiation of antihypertensive drug therapy can help to reduce the burden of hypertension in PLHIV with their inherent increased cardiovascular risk.